EFEKTIFITAS CORPORATE GOVERNANCE PADA HUBUNGAN MANAJEMEN LABA DAN KINERJA KEUANGAN - Irma Deviana, 08.05.52.0175; Hardiningsih, Pancawati (Students Journal of Accounting and Banking, 2013)
This research analyze Earnings Management Influence to financial Performance, Influence Corporate Governance to financial Performance, Influence Corporate Governance to Earnings Management Relationship with financial Performance. Population in observational it is enrolled manufacturing business at Indonesian Stock Exchange (BEI) year 2009-2011 one chose by methods purposive is sampling which is sample chose by sample elect criterion already been determined. Of 160 enrolled manufacturing business at BEI year 2009 2011, base criterion already being established acquired total elected sample available 17 firms each year it, so sample that is utilized (n ) as much 51 (17 x 3 years) observation data. Base observational result and study upon can take conclusion as follows Earnings Management not significant ascendant to financial performance. Corporate governance are not influential significant to financial performance. Corporate governance are not influential significant to Earnings Management relationship with financial performance. That research also proves that corporate governance not such the moderate variable among Earnings Management with financial performance. Keywords: Corporate Governance, Earnings Management, Financial Performance